Method of Collecting and Storing Wheat Grains - Q. A. Davronov; Z.I. Turdimatova (Genius Journals, 2022)
In this article, about the methods and features of wheat grain harvesting, storage, grain harvesting without mechanical damage and foreign impurities is done using modern, highly efficient machines of the American "Cayce" and German "Klass" companies. harvest information is provided.
Keywords: Grain quality; ripening period; shelf life; harvest